Cognitive Development in Infantile-Onset Pompe Disease Under Very Early Enzyme Replacement Therapy. (December 2016) - Lai, Chih-Jou; Hsu, Ting-Rong; Yang, Chia-Feng; Chen, Shyi-Jou; Chuang, Ya-Chin; Niu, Dau-Ming
Most patients with infantile-onset Pompe disease die in early infancy before beginning enzyme replacement therapy, which has made it difficult to evaluate the impact of Pompe disease on cognitive development. Patients with infantile-onset Pompe disease can survive with enzyme replacement therapy, and physicians can evaluate cognitive development in these patients. We established an effective newborn screening program with quick clinical diagnostic criteria. Cognitive and motor development were evaluated using the Bayley Scales of Infant and Toddler Development–Third Edition at 6, 12, and 24 months of age. The patients who were treated very early demonstrate normal cognitive development with no significant change in cognition during this period ( P = .18 > .05). The cognitive development was positively correlated with motor development ( r = 0.533, P = .011). The results indicated that very early enzyme replacement therapy could protect cognitive development in patients with infantile-onset Pompe disease up to 24 months of age.